Protection of transplants against antibody-mediated injuries: from xenotransplantation to allogeneic transplantation, mechanisms and therapeutic insights - Kervella, Delphine; Le Bas-Bernardet, Stéphanie; Bruneau, Sarah; Blancho, Gilles (Frontiers in Immunology, 2022)
Long-term allograft survival in allotransplantation, especially in kidney and heart transplantation, is mainly limited by the occurrence of antibody-mediated rejection due to anti-Human Leukocyte Antigen antibodies. These types of rejection are difficult to handle and chronic endothelial damages are often irreversible. In the settings of ABO-incompatible transplantation and xenotransplantation, the presence of antibodies targeting graft antigens is not always associated with rejection. This resistance to antibodies toxicity seems to associate changes in endothelial cells phenotype and modification of the immune response. We describe here these mechanisms with a special focus on endothelial cells resistance to antibodies. Endothelial protection against anti-HLA antibodies has been described in cellular and animal models, but do not seem to be a common feature in immunized allograft recipients. Complement regulation and anti-apoptotic molecules expression appear to be common features in all these settings. Lastly, pharmacological interventions that may promote endothelial cell protection against donor specific antibodies will be described.